ANALISIS TEGANGAN DAN FLEKSIBILITAS PIPA PADA AREA RUANG POMPA HIDRAN POLITEKNIK PERKAPALAN NEGERI SURABAYA DENGAN MENGGUNAKAN METODE ELEMEN HINGGA - Mahardhika, Pekik; Husodo, Adi Wirawan; Tamimah, Ni'matut; Budiyanto, Ekky Nur; Naufal, Muhammad Ellang; Alam, Hafiz Akbar (P3M Politeknik Negeri Indramayu, 2025)
Hydrant is a fire fighting system. In the process of distributing water in the hydrant fire extinguishing system using piping. The hydrant piping system is a very important piping line in fire prevention, so it must function properly without any problems. The hydrant piping system in this paper is a case of the yard hydrant piping system at the Politeknik Perkapalan Negeri Surabaya. The results of visual inspection on the hydrant piping show that the line pipe is damaged. The line pipe is located in the pump room area. According to DNV D101 that the piping system is a critical line. In this research, an analysis of the stress and flexibility of the pipe in the pump room area will be carried out. Piping around the pump to be analyzed from line numbers 01-101-A53-4” and 01-101-A53-3” to line numbers 02-101-A53-6”. The purpose of this research is to determine whether the line pipe around the hydrant pump is damaged due to stress and flexibility aspects. From the modeling and simulation results, it shows that from the aspect of stress that occurs in the pipe it still meets ASME B31.3 criteria, but from the aspect of flexibility it shows that the pipe is damaged due to displacement and rotation on line 01-102-A53-2